2017
DOI: 10.1186/s12866-017-1024-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, in-vitro virulence traits and antifungal susceptibility pattern of gastrointestinal yeast flora of healthy poultry, Gallus gallus domesticus

Abstract: BackgroundPoultry farming and consumption of poultry (Gallus gallus domesticus) meat and eggs are common gastronomical practices worldwide. Till now, a detailed understanding about the gut colonisation of Gallus gallus domesticus by yeasts and their virulence properties and drug resistance patterns in available literature remain sparse. This study was undertaken to explore this prevalent issue.ResultsA total of 103 specimens of fresh droppings of broiler chickens (commercial G domesticus) and domesticated chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 49 publications
3
38
5
Order By: Relevance
“…In previous research on yeast occurrence in turkey intestinal tracts, Candida was the most frequently isolated genus (22,23). Among Candida species, C. albicans, C. rugosa, C. catenulata, C. glabrata, C. palmioleophila, and C. krusei were isolated in the present study, which were previously noted as constituents of avian microbiota (4,8,10,12,13,25). The results of antifungal susceptibility of Candida species isolated from turkeys' intestinal tracts showed that all isolates were susceptible to voriconazole (≤1 μg/mL), whereas in contrasting findings the chicken Candida isolates susceptibility interval was 0.06-8 μg/mL and C. albicans, C. tropicalis, and C. krusei were among the resistant strains (25).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In previous research on yeast occurrence in turkey intestinal tracts, Candida was the most frequently isolated genus (22,23). Among Candida species, C. albicans, C. rugosa, C. catenulata, C. glabrata, C. palmioleophila, and C. krusei were isolated in the present study, which were previously noted as constituents of avian microbiota (4,8,10,12,13,25). The results of antifungal susceptibility of Candida species isolated from turkeys' intestinal tracts showed that all isolates were susceptible to voriconazole (≤1 μg/mL), whereas in contrasting findings the chicken Candida isolates susceptibility interval was 0.06-8 μg/mL and C. albicans, C. tropicalis, and C. krusei were among the resistant strains (25).…”
Section: Discussionsupporting
confidence: 50%
“…The only analysis of antifungal susceptibility of Candida spp. in poultry isolates was conducted by Subramanya et al (25) in chicken flocks. In previous research on yeast occurrence in turkey intestinal tracts, Candida was the most frequently isolated genus (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The method standardised by Malek et al [ 6 ] was followed to develop biofilms in 96 well microtiter plates. Measurement of biofilm mass by quantitative method was performed using crystal violet for staining the biomass and metabolic activity of the biofilm cells was assessed colorimetrically based on reduction of sodium 39-[1-(phenylamino-carbonyl)-3,4-tetrazolium]-bis(4-methoxy-6-nitro)benzene sulfonic acid hydrate (XTT) as described elsewhere [ 7 ]. Biomass was also demonstrated by fluorescent microscopy with calcofluor white staining (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Candida catenulata is an ascomycetous yeast, commonly associated with dairy products such as milk [ 1 ] and cheese [ 2 , 3 ], including in Ireland [ 4 ]. The species has also been isolated from the microbiota of the oral cavity of female canines [ 5 ], and from the gastrointestinal tract and the feces of poultry [ 6 ], wild birds [ 6 , 7 , 8 ] and piglets [ 9 ]. Its environmental niche is not known, although it has been identified in rural dust [ 10 ] and in the estuary of the river Tagus [ 11 ].…”
Section: Introductionmentioning
confidence: 99%